Uncertainty and the politics of employment protection - Andrea Vindigni (Institute for the Study of Labor (IZA), 2008)
This paper investigates the role that idiosyncratic uncertainty plays in shaping social preferences over the degree of labor market flexibility, in a general equilibrium model of dynamic labor demand where the productivity of firms evolves over time as a Geometric Brownian motion. A key result demonstrated is that how the economy responds to shocks, i.e. unexpected changes in the drift and standard deviation of the stochastic process describing the dynamics of productivity, depends on the power of labor to extract rents and on the status quo level of firing costs. In particular, we show that when firing costs are relatively low to begin with, a transition to a rigid labor market is favored by all and only the employed workers with idiosyncratic productivity below some threshold value. A more volatile environment, and a lower rate of productivity growth, i.e. bad times, "increase the political support for more labor market rigidity only where labor appropriates of relatively large rents. Moreover, we demonstrate that when the status quo level of firing costs is relatively high, the preservation of a rigid labor market is favored by the employed with intermediate productivity, whereas all other workers favor more flexibility. The coming of better economic conditions need not favor the demise of high firing costs in rigid high-rents economies, because good times" cut down the support for flexibility among the least productive employed workers. The model described provides some new insights on the comparative dynamics of labor market institutions in the U.S. and in Europe over the last few decades, shedding some new light both on the reasons for the original build-up of Eurosclerosis," and for its the persistence up to the present day.
urn:nbn:de:101:1-2008060530
Keywords: D71; 330; Employment protection; firing costs; productivity; political economy; rents; volatility; growth; institutional divergence; Kündigungsschutz; Arbeitsmarktflexibilisierung; Hysteresis; Public Choice; Rent Seeking; Lohnbildung; Arbeitsproduktivität; Stochastischer Prozess; Risiko; Theorie; USA; EU-Staaten